Association Between Human Papillomavirus and Transitional Cell Carcinoma of the Bladder - Abdollahzadeh, Pourya; Madani, Seyed Hamid; Khazaei, Sedigheh; Sajadimajd, Soraya; Izadi, Babak; Najafi, Farid (Urology Journal, 2017)
Purpose: Bladder carcinoma is one of the most common malignancies in worldwide. Among several risk factors, Human Papilloma Virus (HPV) have been presumed to play a causative role in the etiology of bladder cell carcinoma. The aim of this study was to evaluate the involvement of HPV infection in biopsy specimens of patients with transitional cell carcinoma at the west of Iran. Materials and methods: In this study, 97 biopsy specimens including 67 patients with transitional cell carcinoma (TCC) of bladder and 30 cases of control group with the mean age of 63 years were studied using immunohistochemistry to identify HPV. Results: 22.4% of patients with TCC of bladder and 3.3% of control group were positive for HPV with a meaningful relation (P=.019). The prevalence of HPV was 4.3 fold higher in men than women. Most TCC patients were belonged to grades II and III. Conclusion: Considering the higher incidence of HPV positivity in patients with TCC of bladder compared to control group, it seems to be a meaningful association between HPV infection and TCC of bladder, at least in the west of Iran.